An Analysis Of Transparency and Accountability in the Village Head’s Role in the Appointment of Village Officials: A Case Study of Desa Jangan-Jangan, Pujananting Subdistrict, Barru Regency - Pananrangi M, A (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aims to analyze the transparency of village head authority management in the appointment of village officials and to identify the inhibiting factors in Desa Jangan-Jangan, Pujananting Subdistrict, Barru Regency. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. Data validity was ensured through credibility, transferability, dependability, and confirmability tests. The findings indicate that the level of transparency in the appointment process is relatively adequate, as reflected by indicators such as the provision of clear information, ease of access, and the existence of mechanisms for reporting violations. However, the lack of collaboration with mass media and non-governmental organizations remains a significant shortcoming. Key barriers include limited public outreach, low community awareness, and insufficient infrastructure. These results highlight the need to strengthen village governance capacity to enhance transparency and accountability in local bureaucratic processes.